The efficacy of crocin of saffron (Crocus sativus L.) on the components of metabolic syndrome: A randomized controlled clinical trial - Tayyebe Kermani; Toba Kazemi; Somayye Molki; Khadije Ilkhani; Gholamreza Sharifzadeh; Omid Rajabi (Journal of Research in Pharmacy Practice, 2017)
Objective: Metabolic syndrome is a set of cardiac risk factors with increased risk of chronic diseases. The aim of this study is to evaluate the efficacy of crocin of saffron on metabolic syndrome. Methods: This double-blind, randomized clinical trial was conducted on metabolic syndrome patients who were randomly assigned to crocin of saffron or control (placebo) groups. The intervention group received 100 mg/day crocin tablets (a constituent of saffron) for 6 weeks. Then, the changes in metabolic syndrome component were compared between two groups. The trial was registered in the Iranian Registry of Clinical Trials. Data were entered to SPSS 15. Chi-square, Fisher's exact, paired t-test, and independent t-test were used to analyze data. P < 0.05 was defined as statistical significant level. Findings: Totally, 48 patients included in the trial (24 intervention and 24 placebo participants). There were significant reductions from baseline measurements in the levels of total cholesterol (P < 0.001) and triglyceride (P = 0.003) after the 6-week crocin administration. However, this decrease in lipid profile was not significant when compared with placebo group. There was no significant change in other laboratory values, blood pressure, and anthropometric measures. Conclusion: The present study indicated that the dose of about 100 mg crocin of saffron was well tolerated and has no complication for 6 weeks of oral administration. However, the dosage used in our study had no effect on metabolic syndrome. Further studies are required to assess this effect with the higher dosages of crocin as well as long time effects of its administration on metabolic syndrome patients.